Proactive personality and career decision self-efficacy: The mediating role of planned happenstance - Felinsa Oktora Tanau; Rose Mini Agoes Salim (HUMANITAS: Indonesian Psychological Journal, 2020)
The junior high school major decision, influenced by personality and capacity, has a subsequent impact on the future careers of the students. This study aimed to identify the mediating role of planned happenstance in the relationship between proactive personality and career decision self-efficacy in junior high school students. As many as 140 junior high school students in Jabodetabek with an average age of 14 years participated in this study. They mainly consist of 9thgrade students (88 females and 52 males). This quantitative study used a non-experimental design, namely the cross-sectional study design. Three adapted measurement tools: career decision selfefficacy short form, proactive personality scale, and planned happenstance career inventory were used to collect the data. Data were analyzed using Haye’s regression techniques to test the mediation. The finding supports the hypothesis, that planned happenstance partially mediates the relationship between proactive personality and career decision self-efficacy. In other words, proactive personality could influence students’ planned happenstance, which ultimately could predict their level of selfefficacy in making career decisions. The implications of the results for the development and preparation for junior high school students are discussed.